(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses issues related to government oversight by world parliaments, including the United States, France, Germany and the Oliy Majlis of the Republic of Uzbekistan, as well as improving the institution of parliamentary oversight to transform our national parliament into a true school of democracy. The issues of establishing effective cooperation mechanisms, improving information technology and state youth policy in parliamentary activities will be studied.